PATCHWORK AND QUILTING BY THE BENEFICIARIES OF SEWING DEPARTMENT IN SOCIAL REHABILITATION CENTER "TARUNA YODHA" SUKOHARJO - Rachmi Kurnia Mulyana; Slamet Supriyadi; Zaini Rohmad (Proceeding of International Conference on Art, Language, and Culture, 2017)
The beneficiaries of sewing department in Social Rehabilitation Centre "Taruna Yodha" Sukoharjo have not fully produce fabric scrap from sewing class. The fabric scraps can be used to make kleenex box and bag by using patchwork and quilting. Making Kleenex box and bag by the beneficiaries was produced by using demonstration method qualitative method to obtain the data. The process of making kleenex box and bag were made in teams. The result of the processes was interesting and unique kleenex boxes and bags made by using fabric scraps which could be sold. The result of making kleenex boxes and bags by using fabric scraps can helps the beneficiaries of sewing department in getting extra payment.